Peningkatan Hasil Belajar Siswa dalam Pembelajaran PKN dengan Menggunakan Pendekatan Kooperatif Tipe Group Investigation (GI) - Silvia Anggreni BP (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to describe whether the use of a group investigation (GI) cooperative approach can improve civics learning outcomes for fifth grade students at SDN 24 Batang Anai. The research method used in this study is a qualitative descriptive method with Classroom Action Research as the type of research. The research data was obtained from test results, the data obtained in the study were analyzed using a qualitative data analysis model. The research results obtained from the use of the group investigation method was an increase in the learning outcomes of class V students at SDN 24 Batang Anai, namely an increase in learning outcomes before the first cycle, namely 60.50 with 42% student mastery, in the first cycle it increased to 70 with 69% student mastery and after correcting the deficiencies of cycle I in cycle II the learning outcomes increased to 80 with 85% student mastery. The conclusion of the study shows that the use of group investigation type cooperative methods can improve student learning outcomes. Keywords: Group investigation, Learning Outcomes, PKn Learning